Progressive retinal atrophy in cats - Wolf, Aida (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2019)
Progressive Retinal Atrophy (PRA) is an umbrella term used to describe a variety of inherited retinopathies observed in multiple species. This literature study focuses on PRA observed in five different cat breeds: Abyssinian, Siamese, Persian, Bengal and African black-footed cat. Various reports have described the mode of inheritance, age of onset, clinical and histological findings and specific genetic mutations seen in these breeds. The similarities and differences of these characteristics among these breeds are discussed.